Serum cytokines elevated during gluten‐mediated cytokine release in coeliac disease. (1st October 2019) - Goel, G.; Daveson, A. J. M.; Hooi, C. E.; Tye‐Din, J. A.; Wang, S.; Szymczak, E.; Williams, L. J.; Dzuris, J. L.; Neff, K. M.; Truitt, K. E.; Anderson, R. P.
Summary: Cytokines have been extensively studied in coeliac disease, but cytokine release related to exposure to gluten and associated symptoms has only recently been described. Prominent, early elevations in serum interleukin (IL)‐2 after gluten support a central role for T cell activation in the clinical reactions to gluten in coeliac disease. The aim of this study was to establish a quantitative hierarchy of serum cytokines and their relation to symptoms in patients with coeliac disease during gluten‐mediated cytokine release reactions. Sera were analyzed from coeliac disease patients on a gluten free‐diet ( n = 25) and from a parallel cohort of healthy volunteers ( n = 25) who underwent an unmasked gluten challenge. Sera were collected at baseline and 2, 4 and 6 h after consuming 10 g vital wheat gluten flour; 187 cytokines were assessed. Confirmatory analyses were performed by high‐sensitivity electrochemiluminescence immunoassay. Cytokine elevations were correlated with symptoms. Cytokine release following gluten challenge in coeliac disease patients included significant elevations of IL‐2, chemokine (C‐C motif) ligand 20 (CCL20), IL‐6, chemokine (C‐X‐C motif) ligand (CXCL)9, CXCL8, interferon (IFN)‐γ, IL‐10, IL‐22, IL‐17A, tumour necrosis factor (TNF)‐α, CCL2 and amphiregulin. IL‐2 and IL‐17A were earliest to rise. Peak levels of cytokines were generally at 4 h. IL‐2 increased most (median 57‐fold), then CCL20 (median 10‐fold). Cytokine changes were strongly correlated with one another, and the most severely symptomatic patients had the highest elevations. Early elevations of IL‐2, IL‐17A, IL‐22 and IFN‐γ after gluten in patients with coeliac disease implicates rapidly activated T cells as their probable source. Cytokine release after gluten could aid in monitoring experimental treatments and support diagnosis. Abstract : Patients with coeliac disease develop acute digestive symptoms after consuming gluten. Coeliac disease and control volunteers consumed gluten, and serial serum cytokine assessments over 6 h defined a consistent cytokine profile that was temporally and quantitatively correlated with timing and severity of symptoms. Cytokine elevation after gluten in patients with coeliac disease were consistent with rapid activation of T cells and has the potential to guide therapeutics development and aid in diagnosis and immune monitoring.